High school student-athletes' perceptions and experiences of leadership as a life skill. (November 2020) - Pierce, Scott; Erickson, Karl; Sarkar, Mustafa
Abstract: Objectives: The purpose of this study was to gain student-athlete perceptions of: (1) the definition of leadership for high school student-athletes; (2) the process of leadership development in high school sport; and (3) the factors that have helped or hindered leadership transfer between high school sport and other life domains. Design: This study was grounded in an interpretivist ontological perspective and used focus group interviews to gather insights of student-athletes' leadership experiences. Method: Purposeful sampling identified 33 high-school student-athlete leaders who were members of student advisory councils for high school state athletic associations in the United States. The 15 females and 18 males participated in focus-group interviews. Reflexive thematic analysis of the interview data was then conducted. Results: Results revealed that student-athlete leadership was viewed as a skill-set and a mindset, driven by individual agency. As an on-going developmental process, student-athletes gained awareness of leadership skills, increased self-expectations and self-confidence in their use and application of leadership skills, and developed a transformational leadership mindset, as they encountered and engaged with critical learning opportunities in high school sport and gained support from coaches and peers. Leadership application outside of sport was a multidimensional psychological process, including both conscious and implicit elements, and facilitated or constrained by environmental opportunities and social influences. Conclusions: High school sport offers a unique context where self-agentic youth leadership development in sport and life can occur through experiential learning opportunities. To this point, future research directions and recommendations for practitioners will be provided. Highlights: Student-athletes viewed leadership as a skillset and a mindset driven by individual agency. Increased awareness, self-expectations and self-confidence helped develop leadership skills. Conscious and implicit states and situational opportunities influenced leadership transfer.